PREPARATION OF A NEW STRUCTURE CREATED FOR SORTING OF GINNING SEEDS - Obidov, Avazbek; Vohidov, Muhiddin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
This paper researches a pilot copy of a seed sorting device with an improved design. In addition, this article has conducted theoretical and practical studies to determine the effectiveness of seed selection. As a result of these studies, the operating mode of the new construction was determined and the parameters for its effective operation were developed. The geometric parameters of the developed sorting device are recommended for use in the production copy.